Dural arteriovenous fistula and sinus thrombosis presenting as parkinsonism and dementia: a case report with literature review - Tu, Ranran; Chen, Qihua; Qin, Lixia (Frontiers in Neurology, 2024)
Introduction: Dural arteriovenous fistula (DAVF) is an uncommon malformation involving an abnormal connection between dural arteries or the pachymeningeal branches of cerebral arteries and dural veins. Its exact pathogenesis remains elusive. Known potential triggers for DAVF include cerebral venous sinus thrombosis (CVST), trauma, ear infections, and cranial surgeries. Due to its rarity and diverse clinical presentations, diagnosing DAVF can be a challenge. Case description: We present a case of DAVF associated with CVST, manifesting as rapidly advancing parkinsonism accompanied by dementia over a month. Brain magnetic resonance imaging (MRI) revealed bilateral symmetric T2 hyperintensities in the basal ganglia and brain stem. Cerebral angiography further confirmed a fistula between the torcular herophili and the transverse-sigmoid sinuses. Despite strong recommendations for transvenous embolization of the fistula, the patient declined the procedure. The anticoagulant therapy and symptomatic treatments administered did not yield any improvement in the patient's condition. In addition, we reviewed 27 DAVF derived parkinsonism and dementia cases. Conclusion: DAVF must be considered in the differential diagnosis for cases of rapidly progressive parkinsonism with concurrent dementia. Given its potential for treatment and reversibility, timely diagnosis and intervention for DAVF are paramount.